Manipulating optical micrograph contrast for visualizing monolayer graphene encapsulated by hBN layers. (10th March 2023) - Kim, Tae-Gwang; Kim, Do-Hoon; Son, Seok-Kyun; Kang, Jang-Won
Abstract: We studied the optical response and visibility of the inside graphene layer in hBN/graphene/hBN on SiO2 /Si substrate, revealing why the graphene layer is invisible on the optical microscope image. The observed behavior of optical response for the hBN/graphene/hBN stack is systematically supported by the calculation and analysis, which investigated the reflectance and contrast spectra based on the matrix method. The substrate effect on the optical response allows us to maximize the contrast of the inside graphene to the hBN layer on the optical micrograph, suggesting a simple approach to make the graphene layer visible.